Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3389/fpubh.2020.00264
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Characteristics and Prognosis Factors of Mild-Moderate Patients With COVID-19 in a Mobile Cabin Hospital: A Retrospective, Single-Center Study

Abstract: Background: Novel mobile cabin hospitals have been built to provide more makeshift beds for patients with COVID-19 in Wuhan. However, the characteristics of these patients needed be further described.Methods: This was a retrospective, single-center study. A total of 869 patients with confirmed COVID-19 were admitted to Wuchang Mobile Cabin Hospital in Wuhan, between February 6th, 2020 and February 20th, 2020. The final date of follow-up was March 6th, 2020. Clinical characteristics and outcome data were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 16 publications
(24 reference statements)
5
37
0
2
Order By: Relevance
“…From our analysis, males were the most affected subjects. This finding agrees with the finding of several studies conducted on other continents, such as China, 10,11,13,13,14 Kuwait, 7 and the United States. 12 Although, during the SARS-CoV pandemic in 2002, there was a female dominance, 22 and in a study of 869 patients confirmed with COVID-19 in Wuhan, China, there were fewer men (43.4%).…”
Section: Publication Biassupporting
confidence: 93%
“…From our analysis, males were the most affected subjects. This finding agrees with the finding of several studies conducted on other continents, such as China, 10,11,13,13,14 Kuwait, 7 and the United States. 12 Although, during the SARS-CoV pandemic in 2002, there was a female dominance, 22 and in a study of 869 patients confirmed with COVID-19 in Wuhan, China, there were fewer men (43.4%).…”
Section: Publication Biassupporting
confidence: 93%
“…Thus, based on the care field selection, which, in the case of this manuscript, is a communicable disease of a pandemic character, nurses will make clinical decisions centered on NP aiming at: a) enhancing the community's response capacity (20) , which has as examples nursing diagnoses, outcomes and interventions aimed at coping; b) supporting the finitude of life and grieving (21)(22) , which has as an example the diagnoses, outcomes and nursing interventions focused on the grieving process; c) reducing the risk for community contamination; d) supporting adaptive processes and their consequences. These objectives are in line with the NOC outcomes presented in RePPE's document.…”
Section: Nursing Diagnosis Outcomes and Interventions For Family/ Comentioning
confidence: 99%
“…The clinical spectrum of patients with COVID-19 appears to be wide, encompassing asymptomatic infection, mild upper respiratory tract illness, and severe viral pneumonia with respiratory failure and even death [ 7 10 ]. Although some case series have been published, knowledge about COVID-19 is still incomplete.…”
Section: Introductionmentioning
confidence: 99%